2012
DOI: 10.1088/2041-8205/747/2/l40
|View full text |Cite
|
Sign up to set email alerts
|

Re-Interpretation of Supra-Arcade Downflows in Solar Flares

Abstract: Following the eruption of a filament from a flaring active region, sunwardflowing voids are often seen above developing post-eruption arcades. First discovered using the soft X-ray telescope aboard Yohkoh, these supra-arcade downflows (SADs) are now an expected observation of extreme ultra-violet (EUV) and soft X-ray coronal imagers and spectrographs (e.g, TRACE, SOHO/SUMER, Hinode/XRT, SDO/AIA). Observations made prior to the operation of AIA suggested that these plasma voids (which are seen in contrast to br… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
142
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 114 publications
(159 citation statements)
references
References 26 publications
15
142
1
1
Order By: Relevance
“…In the late phase of the event, McKenzie and Hudson (1999) found that the downward motion was represented by a dark void in soft X-ray (SXR) moving at speed ranging from 100 to 200 km s −1 , and that the temperature in the void reached up to 9 × 10 6 K, which was slightly hotter than the surrounding fan-shaped supraarcade plasma, and the density was about 10 8 cm −3 . Later, McKenzie (2000) reported 11 long-life CME-associated events observed by Yohkoh/SXT that displayed similar sunward mass motions at speed ranging from 50 to 500 km s −1 , which were also observed recently by the SDO/AIA (Savage et al 2012a). Because of the weak signal of the X-ray data in the void, the temperature deduced for the dark void by McKenzie and Hudson (1999) was somewhat suspect.…”
Section: Downward Reconnection Outflowsmentioning
confidence: 55%
See 4 more Smart Citations
“…In the late phase of the event, McKenzie and Hudson (1999) found that the downward motion was represented by a dark void in soft X-ray (SXR) moving at speed ranging from 100 to 200 km s −1 , and that the temperature in the void reached up to 9 × 10 6 K, which was slightly hotter than the surrounding fan-shaped supraarcade plasma, and the density was about 10 8 cm −3 . Later, McKenzie (2000) reported 11 long-life CME-associated events observed by Yohkoh/SXT that displayed similar sunward mass motions at speed ranging from 50 to 500 km s −1 , which were also observed recently by the SDO/AIA (Savage et al 2012a). Because of the weak signal of the X-ray data in the void, the temperature deduced for the dark void by McKenzie and Hudson (1999) was somewhat suspect.…”
Section: Downward Reconnection Outflowsmentioning
confidence: 55%
“…This is the first time that a survey of ray-like structures has been performed and the results have been compared with CME models, and is also the first time that the CS was recognized by studying the white-light data. With the success of SDO, the CS associated structures right above flare loops have as well been observed in the AIA 131 Å and 94 Å channels in exquisite detail both as rays when viewed edge on (Reeves and Golub 2011), and as fans when viewed face on (Warren et al 2011;Savage et al 2012a;McKenzie 2013). studied the 2002 April 21 event and another two events occurring on July 23 and August 24, 2002, respectively, that all produced X-class (> 1.5) flares with associated fast CMEs at speeds of 1700-2500 km s −1 .…”
Section: Identifications Of the Current Sheet In The Solar Eruptive Ementioning
confidence: 91%
See 3 more Smart Citations